Мода й ритуал: кодекс убрання в Київській Русі - Ричка, В. (Український історичний журнал, 2020)
У статті розглядаються конвенціональні знакові системи кодексу вбрання провідних верств давньоруського суспільства в нерозривній єдності зі сферою їхньої діяльності й поведінки. Мета студії полягає у вивченні комунікативної та символічної природи одягу, осягненні феномену моди у середньовічній Русі та уявлень про сакральну значущість убрання, його ролі в ритуалах щоденної поведінки. Методологічну основу становить принцип історизму, що спирається на впізнаванні релевантної семантичної ізотопії структур повсякденності, комунікативної й ідейно-образної природи вбрання. Наукова новизна. Уперше в українській історіографії комплексно досліджується феномен кодексу вбрання та моди як особливого виду соціальної комунікації Київської Русі. Висновки. З’ясовано комунікативну й символічну природу кодексу вбрання. Одяг і супутні йому речі, що оточували середньовічну людину, мали не тільки утилітарно-споживацький, прагматичний характер – вони диктували манеру поведінки, стиль життя, виконували важливу соціальну функцію. Предметний світ речей і, зокрема, одягу за середньовіччя наділявся знаковим, символічним кодом певних смислів, значень, соціальних комунікацій. Притаманний провідній верстві населення Русі стиль одягання й ритуал щоденної поведінки засвідчував її інтеґрацію у традиції лицарства, феодальної ідентичності. Обґрунтовано, що мода – це не тільки світ речей та одягу в їхніх зовнішніх формах, а ще й жести, зачіски, звичаї, устрій життя, ритуал щоденної поведінки. The article considers the conventional sign systems of the dress code of the leading strata of Rus communities in inseparable unity with the sphere of their activity and behavior. The aim of the research is to study the communicative and symbolic nature of clothing, to understand the phenomenon of fashion in medieval Rus and ideas about the sacred significance of clothing, its role in the rituals of everyday behavior. The methodological basis of the study is the principle of historicism, which is based on the recognition of the relevant semantic isotope of the structures of everyday life, communicative and ideological nature of clothing. The scientific novelty of the work is that it is the first in Ukrainian historiography comprehensive socio-anthropological study of the phenomenon of dress code and fashion as a special type of social communication of Kyivan Rus. Conclusions. The results of the study clarified the communicative and symbolic nature of the dress code. Clothing and related things that surrounded medieval man were not only utilitarian-consumer, pragmatic in nature. They dictated behavior and lifestyle and performed an important social function. The material world of things and, in particular, clothing in the Middle Ages was endowed with a symbolic, symbolic code of certain meanings and meanings and social communications. Each important event in the private and public life of the family, other social groups and professional communities corresponded to his style of dress. The style of dress and ritual of daily behavior inherent in the leading section of the population of Kyivan Rus testifies to its integration into the tradition of chivalry and feudal identity. It is motivated that fashion is not only the world of things and clothes in their external forms, but also gestures, hairstyles, customs, way of life and the whole ritual of daily behavior.